Patterns of genetic diversity and structure in Antarctic and sub-Antarctic Nacella (Patellogastropoda: Nacellidae) species. Issue 1 (2nd April 2016) - González-Wevar, Claudio A.; Hüne, Mathias; Rosenfeld, Sebastián; Saucède, Thomas; Féral, Jean-Pierre; Mansilla, Andrés; Poulin, Elie
Abstract: The biogeography of the Southern Ocean reflects complex interactions between major macro-evolutionary forces and biotic elements. Major gateway openings, the establishment of the Antarctic Circumpolar Current and climate cooling are deeply connected to the composition, abundance and distribution of the Southern Ocean marine benthic fauna. Glacial episodes of the Quaternary heavily impacted the distribution of the genetic variation of the Southern Ocean biota. The genus Nacella includes 12 nominal species in different provinces of the Southern Ocean. In this study, we compared patterns of mitochondrial DNA diversity in three Nacella species from Antarctic Peninsula, Kerguelen Island and Patagonia. Low levels of genetic diversity and absence of genetic structure characterise each one of them showing the strong impact of ice advances and retreats over their respective demographics. Haplotype diversity, short genealogies and demographic inference recorded suggest the occurrence of a more dramatic demographic process in Antarctic Peninsula than in the sub-Antarctic.